The Benefits of Merging Leadership Research and Emotions Research - Humphrey, Ronald H.; Burch, Gerald F.; Adams, Laural L. (Frontiers in Psychology, 2016)
A closer merging of the literature on emotions with the research on leadership may prove advantageous to both fields. Leadership researchers will benefit by incorporating the research on emotional labor, emotional regulation, and happiness. Emotions researchers will be able to more fully consider how leadership demands influence emotional processes. In particular, researchers can better understand how the workplace context and leadership demands influence affective events. The leadership literature on charisma, transformational leadership, leader-member exchange, and other theories have the potential to shed light on how rhetorical techniques and other leadership techniques influence emotional labor, emotional contagion, moods, and overall morale. Conversely, the literature on emotional labor and emotional contagion stands to provide insights into what makes leaders charismatic, transformational, or capable of developing high quality leader-follower relationships. This review examines emotions and leadership at five levels: within person, between persons, interpersonal, groups and teams, and organizational wide and integrates research on emotions, emotional contagion, and leadership to identify opportunities for future research for both emotions researchers and leadership researchers.